Helping women to good health: breast cancer, omega-3/omega-6 lipids, and related lifestyle factors - de Lorgeril, Michel (BioMed Central, 2014)
In addition to genetic predisposition and sex hormone exposure, physical activity and a healthy diet play important roles in breast cancer (BC). Increased intake of omega-3 fatty acids (n-3) associated with decreased omega-6 (n-6), resulting in a higher n-3/n-6 ratio compared with the western diet, are inversely associated with BC risk, as shown by Yang et al. in their meta-analysis in BMC Cancer. High consumption of polyphenols and organic foods increase the n-3/n-6 ratio, and in turn may decrease BC risk. Intake of high fiber foods and foods with low glycemic index decreases insulin resistance and diabetes risk, and in turn may decrease BC risk. The modernized Mediterranean diet is an effective strategy for combining these recommendations, and this dietary pattern reduces overall cancer risk and specifically BC risk. High-risk women should also eliminate environmental endocrine disruptors, including those from foods. Drugs that decrease the n-3/n-6 ratio or that are suspected of increasing BC or diabetes risk should be used with great caution by high-risk women and women wishing to decrease their BC risk. Please see related article: http://www.biomedcentral.com/1471-2407/14/105/abstract.